THE IMPACT ANALYSIS OF MOTIVATION, TRAINING, AND WORK ENVIRONMENT TO NURSES PERFORMANCE IN PATIENT SAFETY - Fushen fushen; Meylona Verawaty Zendrato (Universitas Pasundan, 2019)
The development of hospitals in health industry as economic institutions and the establishment ofmany new hospitals increase the number of nurses needed while the number of nurses producedcannot keep pace with the increasing demand. In hospital services, nurse is the most frequentlyinteracted person with patients and are fully responsible for patient care, including in terms of patientsafety. This study aims to obtain empirical evidence about the effect of motivation, training andwork environment on the performance of nurses in patient safety in the Public Hospital. Expectedoutput from this study can be used as a reference to determine the policy for nurse management atthe hospital. This is a correlational analytic study with a cross-sectional approach and descriptivemethod of verification. The research was conducted in a Public Hospital in Jakarta. The researchsample are 90 nurses working in inpatient wards. The hypothesis of this study were analyzed withpath analysis methods. The results of this study showed a significant positive effect betweenmotivation and performance (20.7%), training and performance (21.8%), working environment andperformance (20.7%), and the simultaneous influence from motivation, training, and workingenvironment on the performance (63.2% ).